When to fight? Disentangling temperature and circadian effects on aggression and agonistic contests. (February 2019) - Nguyen, K.; Stahlschmidt, Z.R.
Abstract : Agonistic behaviour is an important component of intraspecific competition because outcomes of agonistic contests can serve as indicators of fitness, helping the victors secure critical resources. Although several factors affecting aggression, including age and body size, have been well documented, few studies have examined the effects of abiotic factors on aggression and outcomes of agonistic contests. Abiotic factors affect a broad range of behaviours and can naturally covary, but some factors are becoming increasingly uncoupled. For example, ongoing climate change continues to shift temperature, but not light:dark, cycles. Thus, we employed a 2 × 2 factorial design in sand field crickets, Gryllus firmus, to disentangle the naturally covarying effects of temperature and circadian rhythms. During early adulthood, virgin males were maintained in either a typical or inverted diel temperature cycle (i.e. cool in the morning and warm in the afternoon, or warm in the morning and cool in the afternoon, respectively) reflecting field conditions (20.5–32 °C). Agonistic contests occurred at either cool (22 °C) or warm (31 °C) periods in the temperature cycle. Morphological traits, such as head width, femur length and testes mass, positively covaried and influenced the outcome of contests where relatively large crickets won most contests. However, temperature and time of day had additive, interactive effects on the level of aggression and the duration of contests. Contests occurring in cool, morning conditions were relatively long and aggressive. Although crickets appeared to use a mutual assessment strategy (contests between males of mismatched body size took longer to initiate), there may have been a context-dependent shift to a self-assessment strategy during warm evenings. Thus, plasticity in agonistic behaviour occurred due to the interactive, additive effects of temperature and circadian dynamics. We encourage continued investigation into studies that disentangle the effects of temperature and circadian effects on other fitness-related behaviours, such as mate choice or foraging. Highlights: Temperature and time of day interactively affected fighting dynamics in male crickets. Fights were longer and more aggressive in cool, morning conditions. Larger crickets were more likely to win fights. Fights between crickets of mismatched size took longer to initiate.